2017
DOI: 10.3390/ijms18112485
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Molecular Genetics of Basal Cell Carcinoma

Abstract: Basal cell carcinoma (BCC) is the most common human cancer and represents a growing public health care problem. Several tumor suppressor genes and proto-oncogenes have been implicated in BCC pathogenesis, including the key components of the Hedgehog pathway, PTCH1 and SMO, the TP53 tumor suppressor, and members of the RAS proto-oncogene family. Aberrant activation of the Hedgehog pathway represents the molecular driver in basal cell carcinoma pathogenesis, with the majority of BCCs carrying somatic point mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
202
1
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(221 citation statements)
references
References 115 publications
(205 reference statements)
5
202
1
13
Order By: Relevance
“…Our previous finding that PTPN14 is targeted for degradation by high-risk HPV E7 but not by low-risk HPV E7 suggested that PTPN14 loss might be related to the biology of the high-risk HPV (47). PTPN14 is a candidate tumor suppressor based on the observation that it is mutated in some cancers (54,57,(78)(79)(80)(81). The targeted degradation of PTPN14 by high-risk HPV E7 requires the E3 ubiquitin ligase UBR4 and the interaction of UBR4 with papillomavirus E7 is required for E7 to transform cells (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous finding that PTPN14 is targeted for degradation by high-risk HPV E7 but not by low-risk HPV E7 suggested that PTPN14 loss might be related to the biology of the high-risk HPV (47). PTPN14 is a candidate tumor suppressor based on the observation that it is mutated in some cancers (54,57,(78)(79)(80)(81). The targeted degradation of PTPN14 by high-risk HPV E7 requires the E3 ubiquitin ligase UBR4 and the interaction of UBR4 with papillomavirus E7 is required for E7 to transform cells (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Basal cell carcinoma (BCC) is the most common cancer in humans [1]. Although in most cases it does not metastasize, BCC is a significant health issue because it usually appears in exposed skin, and it must be surgically removed to avoid expansion and disfiguration.…”
Section: Introductionmentioning
confidence: 99%
“…The tumor originates from stem cells within hair follicles or the interfollicular epidermis and infundibulum 4,5 . Basal cell carcinoma rarely metastasizes; however, due to sheer number of people affected, the disease poses a considerable health hazard as it causes extensive morbidity through local invasion and tissue destruction 6 . The most common genetic alterations in BCC involve the Hedgehog signaling pathway.…”
Section: Introductionmentioning
confidence: 99%